2022
DOI: 10.1186/s13148-022-01410-8
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of methylation profile in imprinting control regions in human induced pluripotent stem cells

Abstract: Background Parental imprinting is an epigenetic mechanism that leads to monoallelic expression of a subset of genes depending on their parental origin. Imprinting disorders (IDs), caused by disturbances of imprinted genes, are a set of rare congenital diseases that mainly affect growth, metabolism and development. To date, there is no accurate model to study the physiopathology of IDs or test therapeutic strategies. Human induced pluripotent stem cells (iPSCs) are a promising cellular approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…An approach by Pham et al, enabled the generation of iPSC lines with balanced methylation for control purposes and iPSC lines from ID patients with unbalanced methylation. Human iPSCs thus represent a valuable cellular model for investigating the underlying mechanisms of IDs and assessing potential therapeutic strategies in relevant tissues [103].…”
Section: Understanding Genomic Imprinting By Icr and Imprinted Dmrs I...mentioning
confidence: 99%
“…An approach by Pham et al, enabled the generation of iPSC lines with balanced methylation for control purposes and iPSC lines from ID patients with unbalanced methylation. Human iPSCs thus represent a valuable cellular model for investigating the underlying mechanisms of IDs and assessing potential therapeutic strategies in relevant tissues [103].…”
Section: Understanding Genomic Imprinting By Icr and Imprinted Dmrs I...mentioning
confidence: 99%
“…The effect may be due to the antioxidant property of vitamin C; however, a study by Stadtfeld et al confirmed that the addition of ascorbic acid (vitamin C) to the culture media inhibited the loss of imprinting at the DLK1‐DIO3 locus (Esteban et al, 2010; Habib et al, 2014; Stadtfeld et al, 2012). Moreover, adding vitamin C and culturing the iPSCs in hypoxic (5% oxygen) conditions prevented hypermethylation of paternally methylated ICRs such as IG‐DMR, thereby maintaining a normal expression of imprinted genes and pluripotency (Pham et al, 2022). A decade‐old report implicated the importance of the 14q32.2 cluster, specifically SNORD114‐3 and MEG3 , in embryonic stem cells' initial and early passage.…”
Section: Functions Of Dlk1‐dio3 In Pluripotencymentioning
confidence: 99%
“…In the forthcoming years, the AS stem cell model portfolio will likely expand, hopefully encompassing the full spectrum of (epi)genetic variability observed in this condition. Current concerns in the epigenetic and genetic fidelity of human stem cells are being tackled ( Pham et al, 2022 ) and hopefully will be solved in the near future. Also, there are grand expectations for further development of stem cell-based disease modeling with the potential to revolutionize biomedical research, drug development, and, ultimately, patient care.…”
Section: Conclusion Remarks and Future Perspectivesmentioning
confidence: 99%